Gastric-esophageal Junction Outflow Obstruction: Little-known Cause of Dysphagia - Yoandy Hernández Casas; Nélcido Luis Sánchez García; Ulises Periles Gordillo (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Gastric-esophageal junction outflow obstruction is a poorly understood esophageal motor disorder due to its recent identification with the beginning of high-resolution manometry. His ignorance means that it is frequently not noticed in the clinical area. The case of a 34-years-old male patient is presented, who approximately 5 years ago began to sporadically notice a sensation of clogging of solid foods at the thoracic level, sometimes associated with early postprandial vomiting. This manifestation became more frequent a year and a half ago, so he went to the doctor in his province without obtaining a diagnosis or clinical improvement, that is why he was referred to the Gastroenterology Institute. After performing the routine tests in the dysphagia study, the result was obtained by high resolution manometry of an obstruction to the outflow of the gastric esophagus junction. This case presentation can provide to internal medicine specialists with new knowledge so that they take this entity into account in patients with dysphagia where no organic cause is demonstrated. Therefore, the aim of this report is to describe the case of a patient with dysphagia who presents an obstruction to the outflow of the esophagus-gastric junction.